Simple, phosphine free, reusable Pd(II)-2,2 `-dihydroxybenzophenone-SBA-15 catalyst for arylation and hydrogenation reactions of alkenes - Lazar, Anish; Vinod, Chathakudath P.; Singh, Anand Pal (New Journal of Chemistry, 2016)
An efficient, simple, phosphine and co-catalyst free C-C coupling reaction heterogeneous catalyst via a post grafting method is developed and reported. A covalently anchored phosphine free Pd(II) based 2,2'-dihydroxybenzophenone (DHBP) complex over organofunctionalized SBA-15 has been synthesized by the reaction between aminofunctionalized SBA-15 (NH(2)SBA-15) and a 2,2'-dihydroxybenzophenone (DHBP) ligand, and further complexation with Pd(II)Cl-2 to get Pd(II)-DHBP@ SBA-15. The synthesized catalysts were characterized by elemental analysis, XRD, N-2 sorption analyses, TG, DTA, FT-IR, solid state C-13 and Si-29 NMR spectra, XPS, UV-Visible, SEM, EDAX and TEM. The synthesized catalysts were screened in arylation (Heck reactions) and hydrogenation reactions of alkenes, and the results show that Pd(II)-DHBP@ SBA-15 exhibits high conversion and selectivity towards arylation and hydrogenation reactions of alkenes with high stability. The anchored solid catalysts can be recycled effectively and reused several times without major loss in activity.